Bilingual Physical Education in English. Opinion and Qualiication of PE Teachers of Primary Education - López Sánchez, G. F.; Gris Roca, J.; Sánchez Mompeán, S.; Zauder, R.; Smith, L. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The purpose of this research was to survey the opinions of Primary Education PE Teachers about bilingual PE and to find out if they felt confident to teach PE in English. The study sample consisted of 30 individuals, all with a Teaching Diploma in Primary Education (specialty PE). The instrument used was the ’Questionnaire on Bilingual Qualification of Physical Education Teachers’. Statistical analyses were performed through SPSS-22: descriptive statistics, Shapiro-Wilk test, Mann-Whitney U test, and Kruskal–Wallis H test. Most PE teachers surveyed had positive opinions about bilingual PE, but did not have much experience in bilingual teaching and were not sufficiently prepared to deliver classes in English. It would be recommendable to design and carry out educational programs in order to improve the qualification of PE teachers to teach bilingually, checking the effectiveness of these programs.